Negative plate, preparation method thereof and battery

By forming an artificially synthesized in situ SEI film on the surface of lithium metal particles and nano-silicon particles, the problems of unevenness and structural instability of SEI films in lithium metal and silicon negative electrodes are solved, and the rapid migration and cycling performance of lithium ions are improved.

CN119764340AActive Publication Date: 2025-04-04JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411644430.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-04
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The naturally generated SEI films naturally generated during use are uneven composition and unstable structure, resulting in uneven deposition of lithium ions, resulting in dead lithium and lithium dendrites, causing safety problems, and the thickening and breaking of SEI films lead to a decrease in cycle life.

Method used

Lithium metal particles and nanosilicon particles are used, and both surfaces have artificially synthesized in situ SEI films. The SEI film has good ionic conductivity and electronic insulation, inhibiting the direct reduction of lithium ions on the interface, thereby inhibiting the nucleation and growth kinetics of lithium dendrites.

Benefits of technology

The rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode is achieved, cycling performance is improved, the formation of lithium dendrites is inhibited, and the safety and circulation stability of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764340A_ABST
    Figure CN119764340A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative plate, a preparation method thereof and a battery. The negative plate comprises a negative current collector and a composite layer, a first negative electrode active material in the composite layer comprises lithium metal particles and a first SEI film coating the surfaces of the lithium metal particles, and the first SEI film comprises a first functional layer; a second negative electrode active material in the composite layer comprises nano silicon particles and a second SEI film coating the surfaces of the nano silicon particles, and the second SEI film comprises a second functional layer; the first functional layer and the second functional layer independently comprise an A substance and a lithium-containing compound, the A substance comprises an M-containing weak acid salt and / or an M-containing organic salt, and M is Zn and / or Mg. According to the negative plate, rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode can be realized, and meanwhile, direct reduction of the lithium ions on an interface is inhibited, so that lithium dendrite nucleation and growth kinetics are inhibited, and the cycle performance is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] In the next generation of lithium batteries, lithium metal and silicon anodes are considered the focus of battery development. Lithium metal anodes have extremely low electrochemical potential (-3.040V, to standard hydrogen electrode) and extremely high theoretical specific capacity (3860mAh·g -1 ), becoming a key material in lithium metal batteries. However, the traditional lithium metal anode uses lithium foil as the active material, which has a small specific surface area, poor reaction kinetics, and disordered deposition of lithium ions on the surface of lithium foil, resulting in volume changes, and cannot be used in high-rate charge and discharge battery cell design. Silicon anodes have poor conductivity and irreversible capacity decay caused by huge volume expansion during charge and discharge, which limits their further application.

[0003] Lithium metal and silicon negative electrodes will naturally generate SEI films during use. The SEI film components naturally generated by lithium metal and silicon negative electrodes are unevenly distributed between the bulk phases, with unstable structures and poor flexibility. + ) will be unevenly deposited on the surface of the lithium metal negative electrode during migration, resulting in the formation of dead lithium and lithium dendrites. The sharp lithium dendrites will pierce the diaphragm, causing the positive and negative electrodes to short-circuit, thus causing serious safety problems. Moreover, during the process of lithium ion insertion and extraction, the volume expands, causing the SEI film to break, the bulk structure to re-contact with the electrolyte, and the SEI film is regenerated, consuming the electrolyte while the SEI film thickens, increasing R SEI , increasing polarization and reducing cycle life. At the same time, due to the uneven thickness of the SEI film generated by the lithium metal and silicon negative electrode, the local current density is different, the lithium ion deposition rate is inconsistent, and a loose and porous "lithium sponge" is formed on the surface of the lithium metal, which increases the thickness of the battery cell and reduces the cycle performance. In addition, the naturally generated SEI film has poor electrochemical stability and is easily oxidized at high voltage. The SEI film oxidizes and decomposes to produce gas, and is easy to fall off during the cycle, leaking out of the electrode surface, causing the growth of a new SEI film and causing active lithium ion loss. Summary of the invention

[0004] In view of this, the present invention provides a negative electrode sheet, a preparation method thereof and a battery. The negative electrode sheet includes lithium metal particles and nano silicon particles, both of which have an artificially synthesized in-situ SEI film on their surfaces. The SEI film has good ionic conductivity and electronic insulation, and can realize the rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, while inhibiting the direct reduction of lithium ions on the interface, thereby inhibiting the nucleation and growth dynamics of lithium dendrites. Moreover, the in-situ SEI film is evenly distributed between phases, has a stable structure, and good flexibility, which is conducive to improving the cycle performance. Lithium metal particles have a larger specific surface area than lithium foil, which can increase the reactive active area of ​​lithium metal and have good reaction kinetics; lithium metal particles and nano silicon particles are in close contact, which can inhibit the volume expansion of the silicon negative electrode during the charge and discharge process and increase the cycle stability of the silicon negative electrode.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector, and a composite layer disposed on at least one side surface of the negative electrode current collector;

[0007] The composite layer includes a first negative electrode active material and a second negative electrode active material;

[0008] The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer;

[0009] The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer;

[0010] The first functional layer and the second functional layer independently include substance A and a lithium-containing compound, wherein substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg.

[0011] Preferably, substance A includes at least one of silicate, acetate, citrate and lactate.

[0012] Preferably, substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate.

[0013] More preferably, substance A is zinc silicate.

[0014] In the embodiment of the present invention, the lithium-containing compound in the first functional layer and the second functional layer includes an organic salt of lithium, an inorganic salt of lithium, Li 2 At least one of O and LiOH.

[0015] Preferably, the mass ratio of lithium metal particles, nano-silicon particles, substance A and lithium-containing compound is (10-40):(5-30):(5-25g):(0.05-1).

[0016] Preferably, the particle size D of the lithium metal particles is 50 0.1~100μm.

[0017] As a preference, the particle size D of the nano silicon particles 50 It is 50~500nm.

[0018] Preferably, the thickness of the first functional layer and the second functional layer are independently 1 to 500 nm.

[0019] In another embodiment of the present invention, the first SEI film further includes a mixed layer, which is disposed between the lithium metal particles and the first functional layer, and includes a lithium-philic component, a continuous lithium ion-conducting component and a lithium-containing compound.

[0020] In an embodiment of the present invention, the lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg.

[0021] In the embodiment of the present invention, the continuous lithium ion conducting component includes a weak acid salt and / or an organic salt of lithium, Li 2 O and LiOH.

[0022] In an embodiment of the present invention, the lithium-containing compound in the mixed layer includes an organic salt of lithium, an inorganic salt of lithium, Li 2 At least one of O and LiOH.

[0023] Preferably, in the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the lithium-containing compound is (5-50):(5-50):(0.05-1).

[0024] Preferably, the thickness of the mixed layer is 5 to 200 nm.

[0025] Preferably, the thickness ratio of the first functional layer to the mixed layer is (1-100):(1-200).

[0026] In an embodiment of the present invention, the first negative electrode active material and the second negative electrode active material in the composite layer have a compact stacking structure.

[0027] Preferably, the composite layer further comprises a conductive agent and a binder, and the composite layer satisfies at least one of the following (1) to (3):

[0028] (1) The mass ratio of lithium metal particles, nano silicon particles, and conductive agent is (10-40):(5-30):(0.5-3g);

[0029] (2) The mass of lithium metal particles is denoted as m 1 , the mass of the nano-silicon particles is denoted as m 2 , the mass of the conductive agent is denoted as m 3 , m 1 、m 2 、m 3 Satisfies the following relationship:

[0030] 1 / 200≤m 3 / (m 1 +m 2 )≤1 / 20;

[0031] (3) The total mass of the first negative electrode active material, the second negative electrode active material and the conductive agent is denoted as X 1 , the mass of the binder is recorded as X 2 , X 1 , X 2 Satisfies the following relationship:

[0032] 20≤X 1 / X 2 ≤200.

[0033] In a second aspect, the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0034] S1, mixing substance A and an electrolyte to obtain a mixed solution; the electrolyte includes a lithium salt and an organic solvent;

[0035] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg;

[0036] S2, stirring and mixing lithium metal particles, nano-silicon particles and a mixed solution, and then subjecting the mixture to negative charge treatment to obtain a reactant; filtering and drying the reactant to obtain a lithium-silicon composite having an in-situ grown SEI film;

[0037] The lithium silicon composite with an in-situ grown SEI film includes a first negative electrode active material and a second negative electrode active material;

[0038] The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer;

[0039] The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer;

[0040] The first functional layer and the second functional layer independently include substance A and a lithium-containing compound;

[0041] S3, preparing a lithium-silicon composite with an in-situ grown SEI film into a slurry, coating the slurry on at least one side of the negative electrode current collector, and performing a hot pressing process to obtain a negative electrode sheet.

[0042] In an embodiment of the present invention, the lithium salt includes LiFSI, LiPF 6 、LiClO 4 、LiTFSI、LiODFB、LiBF 4 、LiBOB、LiF、LiCl、Li 2 CO 3 , LiOH or at least one of the following.

[0043] Preferably, the concentration of the lithium salt in the mixed solution is 0.5 to 2 mol / L.

[0044] Preferably, the concentration of substance A in the mixed solution is 0.01-0.5 mol / L.

[0045] Preferably, the current of the negative charge treatment is 0.1 to 1 A, and the time of the negative charge treatment is 10 to 90 minutes.

[0046] Preferably, the temperature of the hot pressing treatment is 100 to 180° C., the pressure of the hot pressing treatment is 1 to 20 kPa, and the time of the hot pressing treatment is 5 to 60 min.

[0047] In a third aspect, the present invention provides a battery, which includes the above-mentioned negative electrode sheet, and / or the negative electrode sheet prepared by the above-mentioned preparation method.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The present invention provides a negative electrode sheet with an in-situ grown SEI film, which comprises a negative electrode current collector and a composite layer arranged on at least one side of the negative electrode current collector; the composite layer comprises a first negative electrode active material and a second negative electrode active material; the first negative electrode active material comprises lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film comprises a first functional layer; the second negative electrode active material comprises nano-silicon particles and a second SEI film coated on the surface of the nano-silicon particles, and the second SEI film comprises a second functional layer; the first functional layer and the second functional layer independently comprise a substance A and a lithium-containing compound, and the substance A comprises a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg. The first functional layer coated on the surface of lithium metal particles and the second functional layer coated on the surface of nano-silicon particles are artificially synthesized in-situ SEI films, which have a nano-stacked structure, good ionic conductivity and electronic insulation, can achieve rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, and inhibit the direct reduction of lithium ions on the interface, thereby inhibiting the nucleation and growth dynamics of lithium dendrites. Moreover, the in-situ SEI film has uniform phase distribution, stable structure, good flexibility, and is conducive to improving cycle performance.

[0050] (2) In the present invention, a mixed layer is further included between the lithium metal particles and the first functional layer, and the mixed layer includes a lithium-philic component, a continuous lithium ion-conducting component and a lithium-containing compound. The first functional layer and the mixed layer together constitute a first SEI film. Substance A reacts in situ with the surface of the lithium metal particles to generate a lithium-philic component including M metal and Li-M alloy (where M is Zn and / or Mg), and a weak acid salt and / or organic salt of lithium, Li 2 O and LiOH continuously conduct lithium ions. Among them, the lithium-philic component can induce the uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium-ion conducting component can reduce R SEI (impedance when lithium ions pass through SEI membrane), accelerate the redox reaction at the negative electrode interface. Since the nanoparticle structure of substance A with low crystallinity has a tendency to stack, effective in-situ reaction transformation occurs, forming a dense structure of the lithiated product. At the same time, the lithium-philic component and the continuous lithium-ion-conducting component can reduce the surface resistance while promoting the uniform deposition of lithium ions;

[0051] (3) In the present invention, the volume expansion of nano-silicon particles during the charge and discharge process provides space for lithium ions to transfer in the electrode, forming in-situ pores inside the electrode, thereby promoting the improvement of ion dynamics performance;

[0052] (4) In the present invention, lithium metal particles have a larger specific surface area than lithium foil, which can increase the reactive area of ​​lithium metal and improve the reaction kinetics;

[0053] (5) In step S3 of the preparation method of the present invention, the negative electrode sheet is subjected to hot pressing treatment, and the lithium metal particles are melted and softened. Under the action of pressure, the lithium metal particles and the nano-silicon particles can be in closer contact, which can inhibit the volume expansion of the silicon negative electrode during the charge and discharge process and increase the cycle stability of the silicon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1-1 Schematic diagram of the structure of lithium powder negative electrode material without in-situ reaction and mixed layer.

[0055] Figure 1-2 Schematic diagram of the structure of lithium powder negative electrode material with in-situ reaction and mixed layer.

[0056] Figure 2 Schematic diagram of the structure of nano-silicon negative electrode material.

[0057] Figure 3-1 Schematic diagram of the structure of Li@Si composite electrode.

[0058] Figure 3-2 Schematic diagram of the structure of the composite material in the composite layer of the Li@Si composite electrode.

[0059] Figure 4 SEM image of Li@Si composite electrode. DETAILED DESCRIPTION

[0060] The present invention discloses a negative electrode sheet and a method for preparing the same and a battery. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0061] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.

[0062] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0063] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0064] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0065] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0066] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0067] Specifically, the present invention adopts the following technical solutions:

[0068] In a first aspect, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector, and a composite layer disposed on at least one side surface of the negative electrode current collector;

[0069] The composite layer includes a first negative electrode active material and a second negative electrode active material;

[0070] The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer;

[0071] The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer;

[0072] The first functional layer and the second functional layer independently include substance A and a lithium-containing compound, and substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn (zinc) and / or Mg (magnesium).

[0073] In the present invention, the first functional layer coated on the surface of lithium metal particles and the second functional layer coated on the surface of nano silicon particles are artificially synthesized in-situ SEI films, which have a nano stacking structure, good ionic conductivity and electronic insulation, can realize the rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, and inhibit the direct reduction of lithium ions on the interface, thereby inhibiting the nucleation and growth dynamics of lithium dendrites. Moreover, the in-situ SEI film is evenly distributed between phases, stable in structure, and good in flexibility, which is conducive to improving the cycle performance. At the same time, the negative electrode sheet of the present invention provides space for ion transfer in the electrode by means of the volume expansion of nano silicon particles during the charge and discharge process, forming in-situ pores located inside the electrode, and promoting the improvement of ion dynamics performance; lithium metal particles have a larger specific surface area than lithium foil, which can increase the reactive area of ​​lithium metal and have good reaction kinetics.

[0074] Preferably, substance A includes at least one of silicate, acetate, citrate and lactate.

[0075] Preferably, substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate.

[0076] More preferably, substance A is zinc silicate. Compared with other types of substance A, zinc silicate has a redox potential and metal activity suitable for lithium metal battery systems, so that zinc silicate is more likely to react with the surface of lithium metal particles in situ to generate Zn metal and Li x Zn y Lithium-philic components of alloys and Li x SiO y , Li 2 The continuous lithium-ion-conducting components of O and LiOH. The zinc silicate nanoparticle structure with low crystalline characteristics has a tendency to stack, which enables efficient in-situ reaction transformation to occur and form a dense structure of the lithiated product.

[0077] In the present invention, the first functional layer and the second functional layer include, in addition to substance A, a lithium-containing compound, which is a conventional SEI film component. The lithium-containing compound can effectively prevent further decomposition of the electrolyte and protect the electrode material; regulate the ion transfer rate, improve the energy density and cycle life of the battery; reduce side reactions, and improve the safety and cycle stability of the battery. In an embodiment of the present invention, the lithium-containing compound in the first functional layer and the second functional layer includes organic salts of lithium, inorganic salts of lithium, Li 2At least one of O and LiOH. In the process of preparing the negative electrode sheet, different lithium salts and organic solvents will affect the specific composition of the lithium-containing compound.

[0078] In the embodiment of the present invention, among the specific types of lithium-containing compounds, organic salts of lithium include ROCO 2 Li、ROLi、(ROCO 2 Li) 2 Wherein R is an alkyl group, for example, a methyl group (-CH 3 ), ethyl (-CH 2 CH 3 )wait.

[0079] In the embodiment of the present invention, among the specific types of lithium-containing compounds, inorganic salts of lithium include Li 2 CO 3 , LiF.

[0080] Preferably, the mass ratio of lithium metal particles, nano silicon particles, substance A and lithium-containing compounds is (10-40): (5-30): (5-25g): (0.05-1). Exemplarily, the mass ratio of lithium metal particles, nano silicon particles, substance A and lithium-containing compounds is any value in 30:10:11:0.5, 30:10:22:1, 30:10:5.6:0.25, 30:20:11:0.5, 30:5:11:0.5, 10:30:5:1, 40:5:25:0.05 or any value in the range of any two of the above values. Within this ratio range, the thickness of the first functional layer and the second functional layer can be ensured to be moderate, and the SEI film formed in situ has good ionic conductivity and electronic insulation, which can realize the rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, while inhibiting the direct reduction of lithium ions at the interface, thereby inhibiting the nucleation and growth dynamics of dendrites.

[0081] Preferably, the particle size D of the lithium metal particles is 50 For example, the particle size D of the lithium metal particles is 0.1 to 100 μm. 50 Any value among 0.1 μm, 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any value within the range of any two of the above values. Within this particle size range, the lithium metal particles have a large specific surface area, which can increase the reactive area of ​​the lithium metal and have good reaction kinetics.

[0082] As a preference, the particle size D of the nano silicon particles 50 For example, the particle size D of the nano-silicon particles is 50 to 500 nm. 50The particle size is any value among 50nm, 100nm, 200nm, 300nm, 400nm and 500nm or any value within the range formed by any two of the above values. Within this particle size range, the performance of the lithium silicon composite material is improved.

[0083] Preferably, the thickness of the first functional layer and the second functional layer are independently 1 to 500 nm. Exemplarily, the thickness of the first functional layer and the second functional layer are independently any value among 1 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm or any value within the range of any two of the above values. Within this thickness range, the SEI film formed in situ has good ionic conductivity and electronic insulation, which can realize the rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, while inhibiting the direct reduction of lithium ions at the interface, thereby inhibiting the nucleation and growth dynamics of dendrites. When the first functional layer and the second functional layer are too thick, the energy density of the battery will be lost and the lithium ion transmission efficiency will be reduced; when the first functional layer and the second functional layer are too thin, it will not be able to protect the negative electrode material.

[0084] In another embodiment of the present invention, the first SEI film further includes a mixed layer, which is disposed between the lithium metal particles and the first functional layer, and includes a lithium-philic component, a continuous lithium ion-conducting component and a lithium-containing compound.

[0085] In the present invention, the lithium-philic component in the mixed layer can induce uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium-ion-conducting component can reduce R SEI (impedance when lithium ions pass through SEI membrane), accelerating the redox reaction at the negative electrode interface. Since the nanoparticle structure of substance A with low crystallinity has a tendency to stack, effective in-situ reaction transformation occurs, forming a dense structure of the lithiated product. At the same time, the lithium-philic component and the continuous lithium-ion-conducting component can reduce the surface resistance while promoting the uniform deposition of lithium ions.

[0086] The lithium-containing compound in the mixed layer is a conventional SEI membrane component. The lithium-containing compound can effectively prevent the further decomposition of the electrolyte and protect the electrode material; regulate the ion transfer rate, improve the energy density and cycle life of the battery; reduce side reactions, and improve the safety and cycle stability of the battery.

[0087] In the present invention, the formation mechanism of the lithium-philic component and the continuous lithium-ion-conducting component in the mixed layer is as follows: since lithium is more active than metal M, a redox reaction can occur spontaneously when substance A is attached to the surface of lithium metal particles, and substance A reacts with lithium metal to generate a lithium-philic component and a continuous lithium-ion-conducting component. Among them, the lithium-philic component can induce uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium-ion-conducting component can reduce R SEI(impedance when lithium ions pass through the SEI film), accelerating the redox reaction at the negative electrode interface. Since the nanoparticle structure of substance A with low crystallinity has a tendency to stack, an effective in-situ reaction transformation occurs, forming a dense structure of the lithium product, including the first functional layer and the mixed layer. The product layer porosity is less than 5%. At the same time, the first SEI film of the present invention has good electrochemical compatibility with lithium metal particles, is not easily reduced, and remains stable in long-term cycles.

[0088] In the present invention, the formation mechanism of the lithium-containing compound in the first functional layer, the second functional layer and the mixed layer is:

[0089] (1) Electrolyte decomposition: During the preparation of the negative electrode sheet, the solute in the electrolyte will undergo reduction and decomposition on the surface of the lithium metal particles after negative charge treatment, forming new chemical products, which are then precipitated on the surface of the lithium metal particles.

[0090] (2) Reduction reaction: including the reduction reaction of electrolyte solvent, lithium salt, additives and trace air impurities.

[0091] (3) Specific chemical reactions: components in the electrolyte such as EC, DMC, LiPF 6 etc. will react to form (CH 2 OCO 2 Li) 2 、LiOH、Li 2 CO 3 These substances are deposited on the surface of lithium metal particles to form a conventional SEI film.

[0092] In the embodiment of the present invention, the lithium compound contained in the mixed layer can effectively prevent the further decomposition of the electrolyte and protect the electrode material; adjust the ion transfer rate to improve the energy density and cycle life of the battery; reduce side reactions and improve the safety and cycle stability of the battery.

[0093] In an embodiment of the present invention, the lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg.

[0094] In an embodiment of the present invention, the M metal in the lithiophilic component includes Zn metal and / or Mg metal.

[0095] In an embodiment of the present invention, the Li-M alloy in the lithium-philic component includes a Li-Zn alloy and / or a Li-Mg alloy.

[0096] In the present invention, the "continuous lithium ion conducting component" is equivalent to the SEI film, has the characteristics of a solid electrolyte, is an electronic insulator and Li + Excellent conductor, Li +In the embodiment of the present invention, the continuous lithium ion conducting component includes a weak acid salt and / or organic salt of lithium, Li 2 O and LiOH.

[0097] In the embodiment of the present invention, the weak acid salt or organic salt of lithium in the continuous lithium ion conducting component comprises lithium silicate (Li x SiO y , where 2≤x≤8, 3≤y≤6, for example Li 8 SiO 6 , Li 4 SiO 4 , Li 2 SiO 3 etc.), at least one of lithium acetate, lithium citrate, and lithium lactate.

[0098] In an embodiment of the present invention, the lithium-containing compound in the mixed layer includes an organic salt of lithium, an inorganic salt of lithium, Li 2 At least one of O and LiOH.

[0099] Preferably, in the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the lithium-containing compound is (5-50):(5-50):(0.05-1). Exemplarily, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the lithium-containing compound is any value among 10:10:0.5, 20:30:0.8, 5:50:0.05, 50:5:1 or any value within the range of any two of the above values.

[0100] Preferably, the thickness of the mixed layer is 5 to 200 nm. Exemplarily, the thickness of the mixed layer is any value among 5 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, or any value within the range of any two of the above values. When the mixed layer is too thick, the energy density of the battery will be lost and the lithium ion transmission efficiency will be reduced; when the mixed layer is too thin, it will not be able to protect the negative electrode material.

[0101] Preferably, the thickness ratio of the first functional layer to the mixed layer is (1-100):(1-200). Exemplarily, the thickness ratio of the first functional layer to the mixed layer is any value of 3:5, 1:10, 1:100, 1:200, 1:1, 10:1, 100:1 or any value within the range of any two of the above values. When the thickness ratio of the first functional layer to the mixed layer is controlled within this range, the comprehensive effects of the first functional layer and the mixed layer can be taken into account. On the one hand, the first functional layer is an artificially synthesized in-situ SEI film, which has a nano-stacked structure, good ionic conductivity and electronic insulation, and can realize the rapid migration of lithium ions between the lithium metal negative electrode and the silicon electrode, while inhibiting the direct reduction of lithium ions at the interface, thereby inhibiting the nucleation and growth dynamics of lithium dendrites. Moreover, the in-situ SEI film is evenly distributed between phases, has a stable structure, and good flexibility, which is conducive to improving the cycle performance. On the other hand, the lithium-philic component in the mixed layer can induce uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium-ion conductive component can reduce R SEI (The impedance of lithium ions passing through the SEI membrane) accelerates the redox reaction at the negative electrode interface.

[0102] In the embodiment of the present invention, the substance A in the second functional layer does not react with the nano-silicon particles, so there is no mixed layer between the nano-silicon particles and the second functional layer.

[0103] In the embodiment of the present invention, the first negative electrode active material and the second negative electrode active material in the composite layer have a compact stacking structure, which can reduce the resistance of lithium ions entering and exiting the layer and enhance the ion conductivity.

[0104] Preferably, the composite layer also includes a conductive agent and a binder. Since substance A has the property of conducting ions but not electrons, after substance A is coated on the surface of lithium metal particles and nano-silicon particles, the composite layer conducts ions but does not conduct electrons. Therefore, a conductive agent that plays a conductive role needs to be added to realize the function of conducting electrons.

[0105] Preferably, the composite layer satisfies at least one of the following conditions (1) to (3):

[0106] (1) The mass ratio of lithium metal particles, nano silicon particles, and conductive agent is (10-40):(5-30):(0.5-3g);

[0107] (2) The mass of lithium metal particles is denoted as m 1 , the mass of the nano-silicon particles is denoted as m 2 , the mass of the conductive agent is denoted as m 3 , m 1 、m 2 、m 3 Satisfies the following relationship:

[0108] 1 / 200≤m 3 / (m 1 +m 2 )≤1 / 20;

[0109] (3) The total mass of the first negative electrode active material, the second negative electrode active material and the conductive agent is denoted as X 1 , the mass of the binder is recorded as X 2 , X 1 , X 2 Satisfies the following relationship:

[0110] 20≤X 1 / X 2 ≤200.

[0111] Exemplarily, the mass ratio of lithium metal particles, nano-silicon particles, and conductive agent is any value among 30:10:1, 30:20:0.5, 30:5:1.5, 10:30:0.5, 40:5:3, or any value within the range consisting of any two of the above values.

[0112] For example, m 3 / (m 1 +m 2 ) is any value among 1 / 200, 1 / 150, 1 / 100, 1 / 50, 1 / 40, 1 / 20 or any value within the range formed by any two of the above values.

[0113] For example, X 1 / X 2 The ratio is any value among 20, 25, 40, 60, 80, 100, 120, 140, 160, 180, 200 or any value within the range formed by any two of the above values.

[0114] For the conditions (1) to (2) satisfied by the composite layer, if the proportion of the conductive agent is too high, the energy density of the negative electrode composite layer system will decrease due to the low density of the conductive agent, resulting in battery capacity decay; if the proportion of the conductive agent is too low, the conductivity will be poor, which will affect the overall performance of the battery.

[0115] For the composite layer satisfying condition (3), too much binder will reduce the proportion of active materials and make the electrode brittle; too little binder will result in low peel strength of the electrode and even powder loss during die cutting, increasing side reactions and increasing the short circuit rate of the battery.

[0116] In an embodiment of the present invention, the distribution state of the conductive agent includes at least one of the following:

[0117] (a) a conductive agent is disposed on the surface of the first functional layer and / or the second functional layer;

[0118] (b) The conductive agent is disposed on the surface of the lithium metal particles and / or the nano-silicon particles.

[0119] In an embodiment of the present invention, the conductive agent has a spherical chain structure.

[0120] In a second aspect, the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0121] S1, mixing substance A and an electrolyte to obtain a mixed solution; the electrolyte includes a lithium salt and an organic solvent;

[0122] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg;

[0123] S2, stirring and mixing lithium metal particles, nano-silicon particles and a mixed solution, and then subjecting the mixture to negative charge treatment to obtain a reactant; filtering and drying the reactant to obtain a lithium-silicon composite having an in-situ grown SEI film;

[0124] The lithium silicon composite with an in-situ grown SEI film includes a first negative electrode active material and a second negative electrode active material;

[0125] The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer;

[0126] The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer;

[0127] The first functional layer and the second functional layer independently include substance A and a lithium-containing compound;

[0128] S3, preparing a lithium-silicon composite with an in-situ grown SEI film into a slurry, coating the slurry on at least one side of the negative electrode current collector, and performing a hot pressing process to obtain a negative electrode sheet.

[0129] In an embodiment of the present invention, the lithium salt includes LiFSI, LiPF 6 、LiClO 4 、LiTFSI、LiODFB、LiBF 4 、LiBOB、LiF、LiCl、Li 2 CO 3 The lithium salt can participate in the chemical reaction of forming the artificial SEI film during the negative charge treatment, and can generate a lithium-containing compound after the negative charge treatment, and further form an artificial SEI film with substance A.

[0130] In a specific embodiment of the present invention, the lithium salt includes LiFSI and LiPF 6The two can be combined in any proportion, preferably LiFSI and LiPF 6 The mass ratio is 1:4 to 4:1.

[0131] Preferably, the concentration of the lithium salt in the mixed solution is 0.5 to 2 mol / L. Exemplarily, the concentration of the lithium salt in the mixed solution is any one of 0.5 mol / L, 0.7 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.5 mol / L, 1.7 mol / L, 1.9 mol / L, 2 mol / L, or any value within the range consisting of any two of the above values.

[0132] Preferably, the concentration of the lithium salt in the mixed solution is 0.9 to 1.3 mol / L.

[0133] Preferably, the concentration of substance A in the mixed solution is 0.01-0.5 mol / L. Exemplarily, the concentration of substance A in the mixed solution is any value among 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, or any value within the range consisting of any two of the above values.

[0134] Preferably, the concentration of substance A in the mixed solution is 0.05-0.2 mol / L.

[0135] In a specific embodiment of the present invention, the organic solvent includes ethylene glycol dimethyl ether (DME), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC). However, the types of organic solvents are not limited thereto, and any organic solvent type recognized by those skilled in the art is within the protection scope of the present invention. In the mixed solvent composed of the above organic solvents, the volume ratio of each organic solvent is a conventional ratio, for example, the volume ratio of DME, EC, EMC, DMC, VC and FEC is (10-20): (35-45): (15-20): (15-20): (1-10): (1-10).

[0136] In an embodiment of the present invention, the conductive agent includes at least one of conductive carbon black (Super P), vapor generated carbon fiber (VGCF), graphene, and carbon nanotubes (CNTs).

[0137] In the embodiment of the present invention, in step S2, a conductive agent is added during the negative charge treatment, so that the conductive agent can be evenly distributed on the surface of the lithium metal particles and / or nano-silicon particles, and the generated SEI film is more uniform and stable.

[0138] In an embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride (PVDF), polyethylene terephthalate (PET), polyimide (PI), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), carbonized polyvinylidene fluoride (C-PVDF), poly(acrylamide-co-diallyldimethylammonium chloride) (PAMAC), methyl cellulose (MC), ethyl cellulose (EC), hydroxyethyl cellulose (HEC), polyacrylic acid-sodium carboxymethyl cellulose aqueous copolymer (c-PAA-CMC), and silicon electrode conductive binder (ConductiveBinder-CB).

[0139] Preferably, the current of the negative electricity treatment is 0.1-1A, and the time of the negative electricity treatment is 10-90min. Exemplarily, the current of the negative electricity treatment is any value among 0.1A, 0.2A, 0.3A, 0.4A, 0.5A, 0.6A, 0.7A, 0.8A, 0.9A, 1A, or any value within the range of any two of the above values, and the time of the negative electricity treatment is any value among 10min, 15min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, or any value within the range of any two of the above values.

[0140] Preferably, the temperature of the hot pressing treatment is 100-180°C, the pressure of the hot pressing treatment is 1-20 kPa, and the time of the hot pressing treatment is 5-60 min. Exemplarily, the temperature of the hot pressing treatment is any value in 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or any value in the range of any two of the above values, the pressure of the hot pressing treatment is any value in 1 kPa, 2 kPa, 4 kPa, 5 kPa, 6 kPa, 8 kPa, 10 kPa, 12 kPa, 14 kPa, 16 kPa, 18 kPa, 20 kPa, or any value in the range of any two of the above values, and the time of the hot pressing treatment is any value in 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any value in the range of any two of the above values. In the present invention, the negative electrode sheet is subjected to hot pressing treatment, and the lithium metal particles are melted and softened. Under the action of pressure, the lithium metal particles and nano-silicon particles can be in closer contact, which can inhibit the volume expansion of the silicon negative electrode during the charge and discharge process and increase the cycle stability of the silicon negative electrode.

[0141] In the embodiment of the present invention, step S2 also includes the step of adding a conductive agent, specifically: stirring and mixing lithium metal particles, nano silicon particles, a conductive agent and a mixed solution, and then performing a negative charge treatment to obtain a reactant; filtering and drying the reactant to obtain a lithium silicon composite with an in-situ grown SEI film; the lithium silicon composite with an in-situ grown SEI film includes a first negative electrode active material, a second negative electrode active material and a conductive agent. The conductive agent is added in step S2, and after the negative charge treatment, the conductive agent can be uniformly attached to the surface of the lithium metal particles and the nano silicon particles, so that the first SEI film is more uniform and stable.

[0142] In an embodiment of the present invention, step S3 also includes the step of adding a binder, specifically: preparing a slurry of a lithium-silicon composite with an in-situ grown SEI film and a binder, coating the slurry on at least one side of the negative electrode current collector, and subjecting the slurry to a hot pressing treatment to obtain a negative electrode sheet.

[0143] In an embodiment of the present invention, step S3 is performed in an oxygen-free environment.

[0144] In an embodiment of the present invention, the preparation method of substance A includes: mixing a first salt containing M, ammonium chloride, a second salt containing weak acid radicals and / or organic acid radicals, and a second organic solvent, and subjecting the mixture to ball milling, washing, and vacuum drying to obtain substance A; wherein M is Zn and / or Mg.

[0145] In an embodiment of the present invention, the weak acid radical includes at least one of a silicate radical and an acetate radical.

[0146] In an embodiment of the present invention, the organic acid radical comprises at least one of citrate and lactate.

[0147] In one embodiment of the present invention, the second organic solvent is a mixed solution of water and N-methyl-2-pyrrolidone (NMP) in any proportion. For example, water and NMP are mixed in a volume ratio of 1:1.

[0148] In another embodiment of the present invention, the second organic solvent may be water.

[0149] In an embodiment of the present invention, the rotation speed of the ball milling treatment is 100 to 1000 rpm, and the time of the ball milling treatment is 10 to 20 hours.

[0150] In an embodiment of the present invention, the temperature of the vacuum drying treatment is 50° C. to 120° C., and the time is 1 to 24 hours.

[0151] In a third aspect, the present invention provides a battery, which includes the above-mentioned negative electrode sheet, and / or the negative electrode sheet prepared by the above-mentioned preparation method.

[0152] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.

[0153] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.

[0154] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.

[0155] The present invention will be further described below in conjunction with embodiments:

[0156] Example 1

[0157] The preparation of the negative electrode sheet of this embodiment includes the following steps:

[0158] (1) Preparation method of zinc silicate

[0159] ZnCl 2 (204.0mg), NH 4 Cl (1069.8 mg) and Na 2 SiO 3 9H 2 O (719.6 mg) was dissolved in 10 mL of a mixed solution of deionized water (DIW) and N-methylpyrrolidone (NMP) (V DIW :V NMP =1:1), and then the solution was transferred to a ball mill and ball-milled at 500 rpm for 12 h to synthesize zinc silicate nanoparticles. The product was washed with deionized water in a centrifuge until the supernatant was neutral, washed three times with ethanol, and dried in a vacuum oven at 60°C for more than 12 h. The product was obtained for use.

[0160] (2) Construction of artificial SEI for lithium metal composite anode

[0161] Take LiFSI, LiPF 6 , zinc silicate is dissolved in a mixed solvent with a volume ratio of DME:EC:EMC:DMC:VC:FEC=10:45:15:20:5:5 to prepare a mixed solution. 6 =2:1 (molar ratio), LiFSI and LiPF 6 A total of 1.2 mol / L; zinc silicate 0.1 mol / L.

[0162] Take 500 mL of the mixed solution and place it in a powered stirring device, add lithium powder (D 50 1000nm) 30g, nano silicon (D 5010g of lithium powder negative electrode material (100nm), 1g of conductive carbon black, stirring for 90min, then negatively charging the stirring paddle and stirring tank, current 0.5A, 15min, completing the artificial SEI membrane construction, filtering and drying the sample, and obtaining a composite material including lithium powder negative electrode material and nano-silicon negative electrode material with artificial SEI membrane construction. The structural schematic diagram of the lithium powder negative electrode material is shown in Figure 1-1 (i.e. lithium powder negative electrode material without in-situ reaction and mixed layer) and Figure 1-2 (i.e., a lithium powder negative electrode material with an in-situ reaction and a mixed layer, the thickness of the first functional layer is about 30nm, and the thickness of the mixed layer is about 5nm). The structural schematic diagram of the nano-silicon negative electrode material is shown in Figure 2 (The thickness of its second functional layer is about 30nm).

[0163] (3) Preparation method of lithium silicon composite electrode

[0164] Take 5g of lithium powder negative electrode material and nano-silicon negative electrode material after the artificial SEI film is constructed, 0.2g of binder PVDF, and 5.2g of solvent NMP, mix them evenly and apply them on the surfaces of both sides of the copper current collector. After drying, use a heating plate to hot press the electrode at 100°C and 5Mpa pressure for 5min. The above operations are all completed in an oxygen-free and water-free glove box to prepare a Li@Si composite electrode (negative electrode sheet) with a size of 100mm×55mm. The structural schematic diagram of the Li@Si composite electrode is shown in Figure 3-1 , wherein the structural schematic diagram of the composite material in the Li@Si composite electrode composite layer is shown in Figure 3-2 ; SEM image of Li@Si composite electrode is shown in Figure 4 In this embodiment, both lithium powder and nano-silicon are artificially coated with SEI film, staggered and stacked, the surface of Li@Si composite electrode is compact, and the molded lithium powder can effectively bind the nano-silicon.

[0165] Example 2

[0166] The only difference between this embodiment and embodiment 1 is that:

[0167] In step (2), LiFSI and LiPF 6 , zinc silicate is dissolved in a mixed solvent with a volume ratio of DME:EC:EMC:DMC:VC:FEC=15:40:20:15:5:5 to prepare a mixed solution. 6 =4:1, LiFSI and LiPF 6 A total of 1.3 mol / L, zinc silicate 0.2 mol / L.

[0168] Example 3

[0169] The only difference between this embodiment and embodiment 1 is that:

[0170] In step (2), LiFSI and LiPF 6 , zinc silicate is dissolved in a mixed solvent with a volume ratio of DME:EC:EMC:DMC:VC:FEC=20:35:20:15:5:5 to prepare a mixed solution. 6 =1:2, LiFSI and LiPF 6 A total of 0.9 mol / L, zinc silicate 0.05 mol / L.

[0171] Example 4

[0172] The only difference between this embodiment and embodiment 1 is that:

[0173] In step (2), the amount of nano-silicon added is 20 g, and the amount of conductive carbon black added is 0.5 g.

[0174] Example 5

[0175] The only difference between this embodiment and embodiment 1 is that:

[0176] In step (2), the amount of nano-silicon added is 5 g, and the amount of conductive carbon black added is 1.5 g.

[0177] Example 6

[0178] The only difference between this embodiment and embodiment 1 is that:

[0179] In step (2), zinc silicate is replaced by zinc lactate.

[0180] Comparative Example 1

[0181] The only difference between this embodiment and embodiment 1 is that:

[0182] In step (2), no lithium powder is added.

[0183] Comparative Example 2

[0184] The only difference between this embodiment and embodiment 1 is that:

[0185] In step (2), no nano-silicon is added.

[0186] Comparative Example 3

[0187] The only difference between this embodiment and embodiment 1 is that:

[0188] In step (2), no conductive carbon black is added.

[0189] Comparative Example 4

[0190] The only difference between this embodiment and embodiment 1 is that:

[0191] In step (2), no zinc silicate is added.

[0192] Comparative Example 5

[0193] The only difference between this embodiment and embodiment 1 is that:

[0194] In step (3), the composite material is not subjected to hot pressing.

[0195] Battery preparation and performance testing:

[0196] 1. Preparation of batteries:

[0197] (1) Preparation of positive electrode sheet: NCM811 was used as the positive electrode material. The positive electrode material was mixed with conductive carbon black (SP), lithium titanium aluminum phosphate (LTAP) solid electrolyte, polyvinylidene fluoride (PVDF), etc. at a mass ratio of 96:2:1:1, coated on aluminum foil, and dried and pressed to form a positive electrode sheet with a size of 96 mm × 51 mm.

[0198] (2) Preparation of diaphragm: PP diaphragm is used as the diaphragm.

[0199] (3) Battery assembly:

[0200] The assembly process adopts soft pack lamination. Lamination: stack the positive electrode sheet, diaphragm, and negative electrode sheet in order to obtain a battery cell. Assembly: heat-press the stacked battery cell and put it into the aluminum-plastic film for top and side sealing. Set the charge and discharge cut-off voltage to 1.0-4.2V, the charge and discharge current to 1A / g, and end the test after 2000 cycles.

[0201] 2. Battery performance test:

[0202] (1) Initial efficiency (first effect) test method:

[0203] After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.2V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.2V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 1.0V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 1.0V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharged to 1.0V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated according to (C2+C3+C4) / (C0+C1)×100%.

[0204] (2) 2000 cycles capacity retention rate test method:

[0205] 1). After the capacity division is completed, the battery is first charged to 4.2V with a constant current of 1C, and then charged to I≤0.05C with a constant voltage of 4.2V;

[0206] 2). After standing for 5 minutes, discharge the battery at a constant current of 1C to 1.0V to obtain the discharge capacity C1;

[0207] 3). Let stand for 30 minutes.

[0208] 4). Repeat steps 1)-3) 1999 times to obtain the discharge capacity C2000; the capacity retention rate after 2000 cycles is calculated as (C2000) / (C1)×100%.

[0209] Table 1 Cyclic performance test

[0210]

[0211]

[0212] Note: Since no conductive carbon black was added in Comparative Example 3, electron conduction could not be performed, and therefore the first efficiency and 2000-cycle capacity retention rate data could not be tested.

[0213] It can be seen from the cycle results that compared with comparative examples 1-5, examples 1-6 have the best cycle performance using lithium powder and nano-silicon negative electrodes coated with in-situ SEI films, indicating that the strategy of lithium powder in-situ SEI plus nano-silicon has a significant effect on enhancing electrode kinetic behavior and inhibiting nano-silicon volume expansion.

[0214] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet includes a negative electrode current collector and a composite layer disposed on at least one side surface of the negative electrode current collector; The composite layer includes a first negative electrode active material and a second negative electrode active material; The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer; The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer; The first functional layer and the second functional layer independently include substance A and a lithium-containing compound, wherein substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg.

2. The negative electrode sheet according to claim 1, characterized in that: The substance A includes at least one of silicate, acetate, citrate, and lactate; Preferably, the substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate; More preferably, the substance A is zinc silicate; And / or, the lithium-containing compound in the first functional layer and the second functional layer includes at least one of an organic salt of lithium, an inorganic salt of lithium, Li2O and LiOH.

3. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the lithium metal particles, the nano-silicon particles, the A substance and the lithium-containing compound is (10-40):(5-30):(5-25g):(0.05-1).

4. The negative electrode sheet according to claim 1, characterized in that: The particle size D of the lithium metal particles 50 0.1~100μm; And / or, the particle size D of the nano silicon particles 50 50~500nm; And / or, the thickness of the first functional layer and the second functional layer are independently 1 to 500 nm.

5. The negative electrode sheet according to claim 1, characterized in that: The first SEI film further comprises a mixed layer, the mixed layer is arranged between the lithium metal particles and the first functional layer, the mixed layer comprises a lithium-philic component, a continuous lithium-ion-conducting component and a lithium-containing compound; The lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg; And / or, the continuous lithium ion conducting component comprises a weak acid salt and / or an organic salt of lithium, Li2O and LiOH; and / or, the lithium-containing compound in the mixed layer includes at least one of an organic salt of lithium, an inorganic salt of lithium, Li2O and LiOH; In the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the lithium-containing compound is (5-50):(5-50):(0.05-1); And / or, the thickness of the mixed layer is 5 to 200 nm; And / or, the thickness ratio of the first functional layer to the mixed layer is (1-100):(1-200) 。 6. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material and the second negative electrode active material in the composite layer have a compact stacking structure; And / or, the composite layer further includes a conductive agent and a binder, and the composite layer satisfies at least one of the following (1) to (3): (1) The mass ratio of the lithium metal particles, the nano-silicon particles, and the conductive agent is (10-40):(5-30):(0.5-3g); (2) The mass of the lithium metal particles is recorded as m1, the mass of the nano-silicon particles is recorded as m2, and the mass of the conductive agent is recorded as m3. m1, m2, and m3 satisfy the following relationship: 1 / 200≤m3 / (m1+m2)≤1 / 20; (3) The total mass of the first negative electrode active material, the second negative electrode active material and the conductive agent is denoted as X1, and the mass of the binder is denoted as X2. X1 and X2 satisfy the following relationship: 20≤X1 / X2≤200.

7. A method for preparing a negative electrode sheet, characterized in that: The preparation method comprises the following steps: S1, mixing substance A and an electrolyte to obtain a mixed solution; the electrolyte comprises a lithium salt and an organic solvent; The substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg; S2, stirring and mixing lithium metal particles, nano-silicon particles and the mixed solution, and then subjecting the mixture to negative charge treatment to obtain a reactant; filtering and drying the reactant to obtain a lithium-silicon composite having an in-situ grown SEI film; The lithium-silicon composite with an in-situ grown SEI film includes a first negative electrode active material and a second negative electrode active material; The first negative electrode active material includes lithium metal particles and a first SEI film coated on the surface of the lithium metal particles, and the first SEI film includes a first functional layer; The second negative electrode active material includes nano silicon particles and a second SEI film coated on the surface of the nano silicon particles, and the second SEI film includes a second functional layer; The first functional layer and the second functional layer independently include substance A and a lithium-containing compound; S3, preparing the lithium-silicon composite with the in-situ grown SEI film into a slurry, coating the slurry on at least one side of the negative electrode current collector, and subjecting the slurry to a hot pressing treatment to obtain a negative electrode sheet.

8. The preparation method according to claim 7, characterized in that: The lithium salt includes at least one of LiFSI, LiPF6, LiClO4, LiTFSI, LiODFB, LiBF4, LiBOB, LiF, LiCl, Li2CO3, and LiOH; and / or, the concentration of the lithium salt in the mixed solution is 0.5 to 2 mol / L; And / or, the concentration of the substance A in the mixed solution is 0.01-0.5 mol / L.

9. The preparation method according to claim 7, characterized in that: The current of the negative current treatment is 0.1 to 1A, and the time of the negative current treatment is 10 to 90 minutes; And / or, the temperature of the hot pressing treatment is 100-180° C., the pressure of the hot pressing treatment is 1-20 kPa, and the time of the hot pressing treatment is 5-60 min.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 6, and / or the negative electrode sheet prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Magnesium lithium silicate-coated modified zinc lithium titanate cathode material and preparation method thereof

    CN108899541A

  • Negative electrode material, and electrochemical device and electronic device comprising same

    CN113054167A

  • Preparation method of lithium alloy negative electrode for sulfide all-solid-state battery and sulfide all-solid-state battery

    CN113363427A

  • Preparation method of high-performance lithium battery positive electrode material

    CN116169259A

  • Composite negative electrode material with three-dimensional porous coating as well as preparation method and application of composite negative electrode material

    CN118099398A